Policy Implementation Performance in Developing Countries: The Study of Uganda among East African Countries - Nahikiriza, Daphin (East African Journal of Interdisciplinary Studies, 2023)
This policy paper examines the effectiveness of policy implementation in developing nations, with a focus on Uganda among the East African nations. The performance of Uganda's policy implementation in comparison to other East African nations is highlighted. The World Bank's "Country Policy and Institutional Assessment" (CPIA) for the year 2021 served as the foundation for this desk research. One-way analysis was used in the analysis. The results showed that the East African nations performed better than the global indicator. Kenya earned the highest mean policy implementation score among the three East African nations (3.7539683 on a scale of 1 = low to 6 = high). Kenya came in first, then Uganda (3.4484127), and Tanzania (3.5119048). However, the inconsequential F statistic showed that there is no difference in policy execution between the three states., i.e., the means are equal. There is a general consensus that Uganda has strong policies, but the execution is appalling. The country's policy implementation is better than the average index among developing countries, despite the claim that it might "hold some water." The three nations together with a few others make up the East African countries; while Uganda's performance is lower than Kenya's, it is higher than Tanzania's.